2022
DOI: 10.4142/jvs.21062
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance studies in staphylococci and streptococci isolated from cows with mastitis in Argentina

Abstract: Background Staphylococcus aureus and Streptococcus agalactiae are the main cause of clinical mastitis in dairy cattle in Argentina, whereas coagulase-negative staphylococci (CNS) and environmental streptococci are the main cause of subclinical mastitis. Bacteria isolated from infected animals show increasing antimicrobial resistance. Objectives This study aims to determine the antimicrobial resistance of staphylococci and strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Staphylococci are known to become resistant to several antibiotics, including methicillin resistance, which is important for public health ( 163 , 164 ). Methicillin-resistant Staphylococcus aureus (MRSA) infection can only be treated with limited antibiotics and needs long-term treatment ( 163 , 165–167 ). MRSA infection is zoonotic ( 168 ), and continuous antimicrobial susceptibility surveillance is very crucial to control the transmission of this strain from animal production to humans and vice versa ( 169 ).…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococci are known to become resistant to several antibiotics, including methicillin resistance, which is important for public health ( 163 , 164 ). Methicillin-resistant Staphylococcus aureus (MRSA) infection can only be treated with limited antibiotics and needs long-term treatment ( 163 , 165–167 ). MRSA infection is zoonotic ( 168 ), and continuous antimicrobial susceptibility surveillance is very crucial to control the transmission of this strain from animal production to humans and vice versa ( 169 ).…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%
“…Staphylococci are known to become resistant to several antibiotics, including methicillin resistance, which is important for public health ( 163 , 164 ). Methicillin-resistant Staphylococcus aureus (MRSA) infection can only be treated with limited antibiotics and needs long-term treatments ( 163 , 165–167 ).…”
Section: Control Of Staphylococcal Mastitismentioning
confidence: 99%
“…Antimicrobials are an important tool in mastitis control programs; therefore, surveillance of antimicrobial susceptibility is important to ensure optimal results when using them and minimize the risk of resistance (Bowler et al 2020 ; Kizerwetter-Świda et al 2018 ). Staphylococci can express resistance to a range of antimicrobials, of which methicillin resistance is of public health concern (Crespi et al 2022 ; Fergestad et al 2021 ). Infections caused by methicillin-resistant Staphylococcus (MRS) are more damaging due to the long-term treatments and limited drug options (Adkins et al 2018b ; Crespi et al 2022 ; Mahato et al 2017 ; Virdis et al 2010 ).…”
Section: Non- Aureus Staphylococci and Mammaliicoccimentioning
confidence: 99%
“…Staphylococci can express resistance to a range of antimicrobials, of which methicillin resistance is of public health concern (Crespi et al 2022 ; Fergestad et al 2021 ). Infections caused by methicillin-resistant Staphylococcus (MRS) are more damaging due to the long-term treatments and limited drug options (Adkins et al 2018b ; Crespi et al 2022 ; Mahato et al 2017 ; Virdis et al 2010 ). Recent reports from different parts of the world revealed that MRS are an emerging cause of infection and a potent threat to the dairy industry and public health due to their zoonotic potential (Kizerwetter-Świda et al 2018 ; Windria et al 2016 ).…”
Section: Non- Aureus Staphylococci and Mammaliicoccimentioning
confidence: 99%
“…Regularly monitoring antimicrobial profiles in livestock is very vital to collect data for trends/emergence in antimicrobial resistance genotypes and phenotypes to recognize and identify new or emerging resistance profiles (Crespi et al, 2022).…”
Section: Antimicrobial Resistance By Cow Cns Mastitismentioning
confidence: 99%